Hubungan antara Minda Keusahawanan dan Niat Keusahawanan dalam Kalangan Pelajar dari Universiti Tun Hussein Onn Malaysia - Anim Zalina Azizan; Nurul Safraa Abd Rani (Research in Management of Technology and Business, 2024)
Entrepreneurship plays an important role in fostering economic growth, innovation and job creation. Social problems such as poverty, homelessness and unemployment can also cause consumer spending to be affected and stunt economic growth if the number of entrepreneurs decreases. The objective of this study is to identify the level of entrepreneurial mindset among students from Universiti Tun Hussein Onn Malaysia, to identify the level of entrepreneurial intention among students at Universiti Tun Hussein Onn Malaysia and to identify the relationship between entrepreneurial mindset and entrepreneurial intention among students from Universiti Tun Hussein Onn Malaysia. This study emphasizes the importance of an entrepreneurial mindset in fostering entrepreneurial intentions because students with a high entrepreneurial mindset are more inclined to venture into the field of entrepreneurship. This study uses quantitative techniques in analyzing and obtaining data from respondents. The population of this study is 14,833 students from Universiti Tun Hussein Onn Malaysia (UTHM) at Parit Raja. Therefore, the total sampling is 375 respondents. The results of the data analysis obtained by the respondents are in the form of numbers and statistical data. In addition, descriptive analysis and correlation analysis were also used through the SPSS application. The results of this study can be used as a reference for UTHM students in particular and the findings of this study can encourage entrepreneurial intentions so that UTHM students are active in participating in entrepreneurial activities.